The counties of Nairnshire, Moray and Banffshire in the Bronze Age, Part II - Walker, Iain C (Proceedings of the Society of Antiquaries of Scotland, 1974)
A detailed catalogue and discussion, completed in 1969, of bronzes of the 2nd and early 1st millenia BC found in three counties of NE Scotland. The importance to the area of the Great Glen as a trade route is stressed, and the problem of the origin of metallurgy in NE Scotland is discussed. AR